Teatralidades do real: significados e práticas na cena contemporânea - Julia Guimar?es Mendes (2011)
The goal of this dissertation is to investigate some of the meanings circumscribed in the ways the idea of reality has been explored in theater at the beginning of the current century. The research departs from a bibliographic survey focused in recent publications on the theme, goes through the mapping of the most recurrent appearances of the real at the contemporary scenic and artistic sphere and is concluded with a case study of the play Esta Noite Mãe Coragem (Tonight Mother Courage), by the group ZAP 18 from Belo Horizonte, Minas Gerais. Throughout the work a discussion on the meanings of the growing presence of reality on contemporary theatrical presentation is developed, aiming to focus on a few aspects: In which ways is the real absorbed by theater today? What are the potentialities of such representative strategies? What kinds of questions are elaborated? What reactions are provoked on the spectators? Thus, through this study, it is possible to infer that the presence of the real in the current artistic scenario points both to a new organization of the place of representation in contemporary art as to the reflection about a possible political dimension of theater nowadays.